Hyperoxia increases the elastic modulus of alveolar epithelial cells through Rho kinase. (24th December 2013) - Wilhelm, Kristina R.; Roan, Esra; Ghosh, Manik C.; Parthasarathi, Kaushik; Waters, Christopher M.
<x xml:space="preserve">Abstract</x> Patients with acute lung injury are administered high concentrations of oxygen during mechanical ventilation, and while both hyperoxia and mechanical ventilation are necessary, each can independently cause additional injury. However, the precise mechanisms that lead to injury are not well understood. We hypothesized that alveolar epithelial cells may be more susceptible to injury caused by mechanical ventilation because hyperoxia causes cells to be stiffer due to increased filamentous actin (f‐actin) formation via the GTPase RhoA and its effecter Rho kinase (ROCK). We examined cytoskeletal structures in cultured murine lung alveolar epithelial cells (MLE‐12) under normoxic and hyperoxic (48 h) conditions. We also measured cell elasticity (E) using an atomic force microscope in the indenter mode. Hyperoxia caused increased f‐actin stress fibers and bundle formation, an increase in g‐ and f‐actin, an increase in nuclear area and a decrease in nuclear height, and cells became stiffer (higher E). Treatment with an inhibitor (Y‐27632) of ROCK significantly decreased E and prevented the cytoskeletal changes, while it did not influence the nuclear height and area. Pre‐exposure of cells to hyperoxia promoted detachment when cells were subsequently stretched cyclically, but the ROCK inhibitor prevented this effect. Hyperoxia caused thickening of vinculin focal adhesion plaques, and inhibition of ROCK reduced the formation of distinct focal adhesion plaques. Phosphorylation of focal adhesion kinase was significantly reduced by both hyperoxia and treatment with Y‐27632. Hyperoxia caused increased cell stiffness and promoted cell detachment during stretch. These effects were ameliorated by inhibition of ROCK.